Lexical Competencies For Non-Native Arabic Learnets and Their Nonformity with the Expected Performance of Students “Applied Study” - Ahmet Derviş Müezzin; Mai Gomaa Suhail Gomaa (Darulfunun Ilahiyat)
Vocabulary is the cornerstone of language acquisition and second language learning. Vocabulary allows learners to clearly express their thoughts, opinions, and needs, and a lack of vocabulary or linguistic poverty results in a temporary reluctance to communicate in the target language. No matter how well a student masters grammar, without developing linguistically, they cannot achieve adequate proficiency. This applied study focused on the lexical speaking and writing competencies of (40) preparatory grade students from the Language Center at Ondokuz Mayıs University. A mixed-methods approach was used to examine the vocabulary the learners used as building blocks to develop their mental lexicon and the teaching methods that enhanced their competencies and language skills. A questionnaire was conducted on 40 female graduates from schools for imams and preachers and graduates of Anatolian schools. The questionnaire had seven questions designed to assess the feasibility of the strategies used to improve their language proficiency. Several strategies to raise lexical competency were implemented, the efficiencies of which were determined from an analysis of student questionnaires. This study was important because it sought to identify the reasons for the weak language competencies in some Turkish-speaking students of Arabic, especially in preparatory classes.